Pass the baton of leadership with grace. Issue 6 (22nd January 2018) - Hodges, Dawn Z.
Abstract : Later this year I will retire. It is time for me to pass the baton to my successor. I will be doing so very soon. It will happen prior to my retirement. Because my successor and I will be on campus at the same time, it is extremely important that I pass the baton with grace and dignity.